Green Marketing Strategies for Circular Economy Products: The Moderating Effect of Perceived Greenwashing among Consumers - Meylin Rahmawati; Sulistya Rini Pratiwi; Rizky Agusriyanti Irna; Kartini Kartini; Yohana Thresia Nainggolan; Djuanda Hatta (Global Research Collaboration, 2025)
This study investigates the effects of green marketing strategies namely green brand positioning (GBP), brand storytelling (BST), and consumer environmental knowledge (CEK) on purchase intention (PI) toward circular economy products, with perceived greenwashing (PGW) as a moderating variable. A quantitative survey was conducted with 138 respondents in Tarakan City, North Kalimantan, Indonesia, selected through purposive sampling. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS), including assessment of both measurement and structural models. The measurement model demonstrates satisfactory reliability and validity (CR > 0.70; AVE > 0.50; adequate discriminant validity). Structural results show that brand storytelling has the strongest positive effect on purchase intention (β = 0.387; p < 0.001), followed by green brand positioning (β = 0.298; p < 0.001) and consumer environmental knowledge (β = 0.231; p < 0.01). Perceived greenwashing negatively moderates the relationship between brand storytelling and purchase intention (β = –0.184; p < 0.05), indicating that skepticism toward environmental claims weakens the persuasive impact of brand narratives. The model explains 71.3% of the variance in purchase intention (R² = 0.713). These findings suggest that consumers are willing to support circular products when sustainability claims are perceived as credible.